Answer:
f(x) = 0.43 *
*
*(x + 10)
Step-by-step explanation:
We have a 6th degree polynomial f(x)
r = 3 is a root of f with multiplicity 2
r = 1 is a root of f with multiplicity 3
f(-5) = -29721.6
f(-10) = 0
Then: f(x) = a*((x -3)^2 ) * ((x - 1)^3)*(x + 10)
f(-5) = a * (-8)^2 * (-6)^3 * (5) = -29,721.6
a* (64) * (-216)* 5 = -29,721.6
-a*69,120 = -29,721.6
a = -29,721.6/-69,120
a = 0.43
so
f(x) = 0.43 *
*
*(x + 10)
Answer:
1. 72, 2. 36, 3. 80, 4. 54
Step-by-step explanation:
You have to draw a line of Justin’s kitchen and then draw his modern table hire an artist to do it for you hope that helps
Answer: 11/4
or 2.75
Step-by-step explanation:
Answer:
The extraneous solution is 4.
Step-by-step explanation:
First, let us calculate the value of 'x' without squaring both side of the expression. This is illustrated below:
-5 = 3x - 7
Collect like terms
-5 + 7 = 3x
2 = 3x
Divide both side by 3
x = 2/3.
Now, let us calculate the value of 'x' by squaring both side of the expression. This is illustrated below:
(-5)^2 = (3x - 7)^2
25 = (3x - 7)(3x - 7)
25 = 9x^2 - 21x - 21x + 49
9x^2 - 42x + 49 - 25 = 0
9x^2 - 42x + 24 = 0
Solving by factorisation:
Multiply the first term i.e 9x^2 and 3rd term i.e 24 together. The result is 216x^2.
Next, we shall obtain two factors of 216x^2 such that when we add them together, it will give the 2nd term i.e -42x in the equation. These factors are: -6x and -36x
Now we can write the above equation as:
9x^2 - 42x + 24 = 0
9x^2 - 6x - 36x + 24 = 0
3x(3x - 2) - 12(3x - 2) = 0
(3x - 12)(3x - 2) = 0
3x - 12 = 0 or 3x - 2 = 0
3x = 12 or 3x = 2
x = 12/3 or x = 2/3
x = 4 or 2/3.
We can see that when we solve the question without squaring both side, the value of x is 2/3. But when we solve by squaring both side, the value of x are 4 and 2/3.
Therefore, the extraneous solution to the question is 4.